THE ANTI-INFLAMMATORY EFFECT OF GARDI PATCH IN CARRAGEENAN-INDUCED PAW EDEMA OF RATS - Dejidmaa B; Uuganbayar B; Erdenechimeg Ch; Chimedragchaa Ch; Munkhzul G (Proceedings of the Mongolian Academy of Sciences, 2018)
Gardi -5 has been used in traditional Mongolian medicine as an analgesic and antibacterial medicine. The drug has been studied in chemical-pharmacological research. We have a new natural patch from the prepared Gardi-5. The present work was undertaken to evaluate the traditional drug Gardi patch for its anti-inflammatory activity. The method of Miho Sekiquichi was used to study acute inflammation. Rats in groups of five each were treated with vehicle, Gardi patch and Ketoprofen patch one hour prior to Carrageenan injection. 0.1 ml of 1% Carrageenan was injected into the sub plantar tissue of left hind paw of each rat. Swelling of carrageenan injected foot was measured at 0, 30, 60, 120, 180, 240, 300 mins using Plethysmometer (UGO Basile, Italy). The right hind paw was injected with 0.1 ml of vehicle. The Gardi patch significantly (p=0.000) inhibited carrageenan induced rat paw edema as compared to control group. In assay data, the TNF-α, PGE2 secretion in serum were highly elevated by carrageenan induction but administration of Gardi patch significantly reduced serum secretion of inflammatory mediators as compared to vehicle group. Gardi patch has an anti-inflammatory properties.